Characterization of a new hexaploid triticale 6D(6A) substitution line with increased grain weight and decreased spikelet number - Zhiyu Feng; Zhongqi Qi; Dejie Du; Mingyi Zhang; Aiju Zhao; Zhaorong Hu; Mingming Xin; Yingyin Yao; Huiru Peng; Qixin Sun; Zhongfu Ni (Crop Journal, 2019)
Hexaploid triticale (×Triticosecale, AABBRR) is an important forage crop and a promising energy plant. Transferring D-genome chromosomes or segments from common wheat (Triticum aestivum) into hexaploid triticale is attractive in improving its economically important traits. Here, a hexaploid triticale 6D(6A) substitution line Lin 456 derived from the cross between the octoploid triticale line H400 and the hexaploid wheat Lin 56 was identified and analyzed by genomic in situ hybridization (GISH), fluorescence in situ hybridization (FISH), and molecular markers. The GISH analysis showed that Lin 456 is a hexaploid triticale with 14 rye (Secale cereale) chromosomes and 28 wheat chromosomes, whereas non-denaturing fluorescence in situ hybridization (ND-FISH) and molecular marker analysis revealed that it is a 6D(6A) substitution line. In contrast to previous studies, the signal of Oligo-pSc119.2 was observed at the distal end of 6DL in Lin 456. The wheat chromosome 6D was associated with increased grain weight and decreased spikelet number using the genotypic data combined with the phenotypes of the F2 population in the three environments. The thousand-grain weight and grain width in the substitution individuals were significantly higher than those in the non-substitution individuals in the F2 population across the three environments. We propose that the hexaploid triticale 6D(6A) substitution line Lin 456 can be a valuable and promising donor stock for genetic improvement during triticale breeding. Keywords: In situ hybridization, Spikelet number, Substitution line, Thousand-grain weight, Triticale